Supporting Pioneering Leaders as Communities of Practice - How to Rapi dly Develop New Leaders in Great Numbers - Wheatley, Margaret J (The Berkana Institute, 2002)
Do you ever stand back and try to see the big picture, the view from 5 0,000 feet of what's going on in organizations, communities, the world ? From up there, how would you describe these times? Is it a time of i ncreasing economic and political instability, of growing divisiveness and fear, of failing systems and dying dreams? Is it a time of new pos sibilities, of great examples of hope, of positive human evolution, of transformation? Are we succeeding in solving major problems, are we c reating more? Is it any of these things, is it all of these things? It 's important to think about how we answer this question, because that answer affects our choice of actions. If we think that, generally, thi ngs are working, that at present we're going through a difficult but t emporary downturn, then we don't question current systems or their ope rating assumptions. Instead, we work hard to revive and improve them. We support initiatives and programs focused on process improvements, d eveloping present systems to work more effectively and more efficientl y. If we believe that the old system cannot be repaired, if we expect to see only more system failures, then the work is not to fix. Instead , support needs to be given to radically different processes and metho ds, new systems based on new assumptions. The work becomes not process improvement but process revolution.